Trilobatin ameliorates HFD/STZ-induced glycolipid metabolism disorders through AMPK-mediated pathways. (April 2023) - Zhong, Yu-te; Shen, Qiong; Yang, Yu-ting; Zhang, Ruo-bing; Zhao, Li-chun; Li, Wei
Graphical abstract: Highlights: As a dihydrochalcone, trilobatin has the ability to improve liver lesions caused by a high-fat diet. Trilobatin has an ameliorative effect on insulin resistance due to a high-fat diet. The mechanism by which trilobain ameliorates glycolipid metabolism disorder is associated with AMPK-mediated energy metabolic pathways. Trilobatin has an ameliorating effect on STZ-induced disorders of glucose tolerance and insulin tolerance. Abstract: Lithocarpus polystachyus Rehd is a sweet tea passed down from the folklore of southern China and is said to be effective in emaciation-thirst disease, which traditional Chinese medicine considers as diabetes. In the present study, we purified the major dihydrochalcone compound trilobatin (TRI) from sweet tea. Besides, a high-fat diet (HFD) combined with streptozotocin (STZ) induced type 2 diabetic mice model was used to investigate the effect of TRI in preventing glycolipid metabolism disorder. According to the results, TRI administration provided some improvement in elevated blood lipids, liver function, fatty liver, glucose metabolism disorders, and insulin sensitivity. These results demonstrated that TRI suppresses glycolipid metabolism disorder. According to the western blotting results, TRI stimulates AMPK and ACC phosphorylation while inhibiting the production of PGC-1α, PCK1, and G6Pase. Thus, AMPK-mediated gluconeogenesis and fatty acid anabolism may be inhibited by TRI, which may be the mechanism that TRI ameliorates glycolipid metabolism disorder.